Swift personal emergency help facilitated by the mobile cloud. (2018) - Alshareef, Hazzaa; Grigoras, Dan
Many emergency cases require the swiftest possible response from an appropriate medical service if they are not to become life-threatening. In the medical emergency field, response times to emergency cases are a major concern and gain a high degree of attention. Many of the systems proposed in the literature are either intended to replace the existing emergency system with a fully automated one, or build on unreliable or less efficient frameworks that are based on some sort of social media application, such as redirecting emergency requests to Facebook friends. We have designed a mobile cloud service that works side by side with the existing emergency system and is aimed at reducing the time spent waiting for emergency help to arrive, as well as making the best use of medical professionals who may be located in close proximity to the medical case. The experimental results show that the amount of time needed to find a medical professional and establish communication was between 4 and 25 seconds, depending on the communication method used. This result means that no extra time is added to the total medical response time and could enhance the chance of a better outcome.